PERANAN AUDIT INTERNALTERHADAP PEMBERIAN FASILITAS LOAN ON CARD PADA PT. BANK MEGATBK - Rosalia Irawaty (Sekolah Tinggi Manajemen IMMI, 2019)
The research objectives in this study 1). Analyzing the suitability of the application of policies and procedures at PT. Bank Mega Tbk Directorate of Credit Cards in relation to the control process and Bank Indonesia Regulation (PBI) 2). Analyzing the implementation of the Loan On Card Facility application is in accordance with operational policies and the Standard Operating Procedure. 3). Analyzing the effect of internal audit on the provision of Loan On Card facilities at PT. Bank Mega Tbk. The method used in this study is descriptive qualitative. This study does not use hypotheses, but only describes the information as it is in accordance with the variables studied. The approach used in this study is a case study, in this case the author will describe the Role of Internal Audit Against the Granting of Loan On Card Facility where the object of research is PT. Bank Mega Tbk. The results of the study are: 1). Provision of Loan On Card Facility at PT. Bank Mega complies with Bank Indonesia regulations. This can be proven by giving the limit given for each account is 50% (fifty percent) of the available limit 2). PT. Bank Mega Tbk has provided Loan On Card Facilities in accordance with the Loan On Card. For some accounts that are not in accordance with MPM- CARO-13-03 because the cardholder already has another card (second card) and has met the criteria determined with the assumption of low risk because the limits set for each cardholder are based on the account, not per product 3). The Audit Team is proven to have an important role related to the provision of Loan On Card facilities, which is directly related to the prevention of fraud in all its forms or expansion in every activity studied. Based on the results of the audit and recommendations, PT. Bank Mega can find out the shortcomings that must be corrected and can equip the organization with analysis, assessment, recommendations, consultations and information about the activities studied. The recommendations that can be given are 1). For the Audit team, you should not only conduct periodic reviews, ie once a year. This is considered to be ineffective due to the rapid development of business. 2). For companies, they are expected to pay more attention to the rules of Bank Indonesia, by granting maximum limits on Loan On Card facilities. 3). This research needs to be further developed by adding other variables so that the results of the study are more perfect and can be useful for the reader